Effective role of mineral oil and biological nanomaterial on thermal energy influenced by magnetic dipole and nanoparticle shape - Nazir, Umar; Sohail, Muhammad; Naz, Samaira; Mukdasai, Kanit; Singh, Manoj; Singh, Abha; Mohan, Chandika Rama; Eldin, Sayed M.; Galal, Ahmed M. (Frontiers in Materials, 2023)
The researchers got special consideration on using nanoparticles for the impact of thermal performance. This study is conducted to describe heat and mass transfer by implicating the involvement of magnetic dipole on chemically reactive species for two-dimensional steady incompressible flow. The involvement of heat generation is incorporated in the energy equation, while, first order chemical reaction is involved in the mass transport phenomenon. The concept of the boundary layer is adopted to derive the physical problem in Cartesian coordinates which results in the form of coupled partial differential equations (PDEs). The derived PDEs are highly nonlinear and an exact solution is not possible. Due to difficulties in solution, these PDEs have been converted into nonlinear ordinary differential equations (ODEs) by using appropriate similarity transformation and then solved numerically via the finite element method. The impact of numerous emerging parameters on the solution is displayed graphically and discussed their physical significance.